IMPLEMENTATION OF THE COURSE “NEW PEDAGOGICAL TECHNOLOGIES ”AS A FACTOR OF INCREASE PROFESSIONALISM OF FUTURE TEACHERS - Savchenko, L.O. (Pedagogy of Higher and Secondary Education, 2022)
The problem of the improvement of the content of the future teacher’s training is given in this article. The experiment of teaching o f the course “New pedagogical technologies” is given there.